Case Report: Pneumocystis jiroveci pneumonia: report of five children with the nephrotic syndrome and review of the literature - Han, Peitong; Yuan, Xiaoying; Li, Chunzhen; Zhang, Lei; Cui, Jieyuan (Frontiers in Pediatrics, 2025)
ObjectiveTo retrospectively analyze the clinical characteristics, treatment, and prognosis of five pediatric patients with nephrotic syndrome who developed Pneumocystis carinii pneumonia (PJP) after long-term use of steroids and tacrolimus.MethodsA review was conducted on five cases of nephrotic syndrome in children who developed Pneumocystis pneumonia after long-term treatment with steroids and tacrolimus. The initial symptoms, early clinical characteristics, and imaging changes were summarized. Among these cases, two were diagnosed through alveolar lavage fluid metagenomic testing and three through sputum metagenomic testing (BGI Genomics Co.), all indicating (pneumocystis carinii pneumonia. All five patients received early treatment with sulfa drugs, with three of them also receiving caspofungin.ResultsOne child died and four were discharged with symptomatic improvement.ConclusionPJP is a severe opportunistic infection that can progress rapidly and lead to life-threatening respiratory failure, particularly in immunocompromised individuals. Among children with nephrotic syndrome (NS), prolonged exposure to glucocorticoids, tacrolimus, or other immunosuppressive agents markedly increases susceptibility to PJP. Therefore, heightened clinical vigilance, early etiological diagnosis, and prompt initiation of appropriate therapy are essential to improving clinical outcomes in this population.